Hedgehog stimulates maturation of Cubitus interruptus into a labile transcriptional activator. - Ohlmeyer, J.T.; Kalderon, D. (Nature, 1998)
In Drosophila, signalling by the protein Hedgehog (Hh) alters the activity of the transcription factor Cubitus interruptus (Ci) by inhibiting the proteolysis of full-length Ci (Ci-155) to its shortened Ci-75 form. Ci-75 is found largely in the nucleus and is thought to be a transcriptional repressor, whereas there is evidence to indicate that Ci-155 may be a transcriptional activator. However, Ci-155 is detected only in the cytoplasm, where it is associated with the protein kinase Fused (Fu), with Suppressor of Fused (Su(fu)), and with the microtubule-binding protein Costal-2. It is not clear how Ci-155 might become a nuclear activator. We show here that mutations in Su(fu) cause an increase in the expression of Hh-target genes in a dose-dependent manner while simultaneously reducing Ci-155 concentration by some mechanism other than proteolysis to Ci-75. Conversely, eliminating Fu kinase activity reduces Hh-target gene expression while increasing Ci-155 concentration. We propose that Fu kinase activity is required for Hh to stimulate the maturation of Ci-155 into a short-lived nuclear transcriptional activator and that Su(fu) opposes this maturation step through a stoichiometric interaction with Ci-155.